Teaching to Research: The Use of Gamification in Pedagogical Experiences - Pereira, Gleice; Berti, Ilemar Christina Lansoni Wey; Andrade, Morgana; Barros, Victor; Caetano, Alessandra Monteiro Pattuzzo; Silva, Rosângela; Valente, Vania [UNESP]; Paletta, Francisco Carlos (My University, 2024)
The pedagogical practice aimed at strengthening sustainable societies, calls for the active participation of student in projects on the environment and sustainable forms of interaction of subjects with spaces, means of production, and consumption. These pedagogical proposals encourage the creation of favorable environments of reflection and the participation of students in seeking creative solutions, activated by curiosity and the desire to know and solve socio-environmental problems. The literature points to the relevance of developing research in schools where the teacher values and performs the awakening of students to curiosity and the creation of socio-environmental solutions, by providing activities that stimulate the development of research projects through the learning of Scientific Methodology. It is in this context that gamification appears as an innovative and promising solution in the educational segment. This article is part of the project that aims to propose gamification resources to be applied in schools, directed to the development of informational and research skills for students from 6th to 9th grade, with applicability in school libraries. The gamification process foresees as products the elaboration of a board game, which initially will be the basis for the development of a virtual game, and a model of good practices for the incorporation of gamification of scientific research methodology for schools and public and private libraries. Contemporaneity brings us challenges that interpose between educational policies and teaching practices, provoking, in an unconventional way, the integration of sustainability with education in a student-centered way, where he becomes the protagonist of his learning, using methods and methodologies such as: case study, problem-based learning and games. The teaching of sustainability in schools is relevant to form individuals with leadership, criticism, and capable of dealing with social and socio-environmental complexities. It is a school education guided by ethical and responsible principles in relation to the environment, with a focus on sustainable societies, which reflect on global but also local aspects, understood by the ways of being connected with citizen action and what societies produce and consume. In this sense, the school assumes a fundamental role, becoming one of the pillars for the construction of values and the formation of the individual as a conscious and responsible being. The gamification adopted for an entrepreneurship education seeks to integrate sustainability with teaching in a student-centered way by offering innovative solutions and actions from an early age, awakening strategic planning and critical thinking, which are skills and competencies needed everywhere in current society. In this article the preliminary results of the study are presented, as well as the actions planned for the realization of the project.
Keywords: Elementary School—final years (6th to 9th grade); Gamification; Libraries; Scientific research methodology